2021
DOI: 10.1128/spectrum.01571-21
|View full text |Cite
|
Sign up to set email alerts
|

A-to-I mRNA Editing in a Ferric Siderophore Receptor Improves Competition for Iron in Xanthomonas oryzae pv. oryzicola

Abstract: Adenosine-to-inosine (A-to-I) RNA editing, which is catalyzed by the adenosine deaminase RNA-specific family of enzymes, is a frequent posttranscriptional modification in metazoans. Research on A-to-I editing in bacteria is limited, and the importance of this editing is underestimated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(22 citation statements)
references
References 55 publications
2
20
0
Order By: Relevance
“…Besides, tadA can be completely knocked out in Xoc, which suggests the existence of an isoenzyme of TadA in Xoc. It is consistent that A-to-I editing events at position A 34 of tRNA Arg are still observed in RNA-seq data of the knockout tadA mutant (Nie et al, 2021). In addition, we demonstrated that the A-to-I mRNA editing event on xfeA leading to a threonine to alanine mutation (T408A) is independent of tadA in Xoc, but the editing site has the same secondary structure and most preferred motif UACG as the TadA-independent A-to-I mRNA editing events (Nie et al, 2021).…”
Section: Enzymes That Mediate A-to-i Rna Editing In Bacteriasupporting
confidence: 85%
See 3 more Smart Citations
“…Besides, tadA can be completely knocked out in Xoc, which suggests the existence of an isoenzyme of TadA in Xoc. It is consistent that A-to-I editing events at position A 34 of tRNA Arg are still observed in RNA-seq data of the knockout tadA mutant (Nie et al, 2021). In addition, we demonstrated that the A-to-I mRNA editing event on xfeA leading to a threonine to alanine mutation (T408A) is independent of tadA in Xoc, but the editing site has the same secondary structure and most preferred motif UACG as the TadA-independent A-to-I mRNA editing events (Nie et al, 2021).…”
Section: Enzymes That Mediate A-to-i Rna Editing In Bacteriasupporting
confidence: 85%
“…The chemotaxis of the pre-edited version of the strains to attractants (glucose, serine, Fe-Ent, and phosphate buffer) relative to glucose was measured using capillary chemotaxis experiments (Verma et al, 2018), and it was found that the T408A edited strain was stronger than the pre-edited version. Fe-Ent induces a more pronounced chemotactic response, suggesting that the xfeA T408A editing event enhances the bacterial chemotactic response to Fe-Ent, which in turn facilitates bacterial uptake of iron (Nie et al, 2021). Iron uptake and chemotaxis are critical for strain pathogenicity in bacteria (Qian et al, 2009;Muok et al, 2019), and most bacteria deal with iron abundance and shortage via the iron uptake factor (Fur) (Hantke, 2001;Troxell and Hassan, 2013).…”
Section: The Function and Meaning Of A-to-i Rna Editing In Bacteriamentioning
confidence: 99%
See 2 more Smart Citations
“…(2) Bacteria transport intracellular FAD to periplasmic space, and then hydrolyze to FMN, which is released into the extracellular environment through pore-forming proteins in the outer membrane and acts as electron shuttle carrier to transport electrons ( Grill et al, 2007 ). In addition, siderophores synthesized intracellularly by bacteria could be secreted to capture Fe(III) in the extracellular environment, enabling them to achieve specific chelation of Fe(III) even under low Fe(III) conditions ( Nie et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%